(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to investigate the effect of circuit training on physical condition improvement among football players in Lubuk Beringin Village. Physical condition is a fundamental aspect that supports technical, tactical, and mental performance in football. The research employed an experimental design with pretest-posttest measurements involving 20 male football players aged 23 years. The circuit training program consisted of 8 stations performed 3 times per week for 6 weeks, with each station lasting 30 seconds to 1 minute. Physical condition was measured through six tests: push-ups, sit-ups, pull-ups, 40-meter sprint, Illinois agility run, and 2400-meter run. Data were analyzed using the Wilcoxon non-parametric test and Levene’s test for homogeneity. The results showed significant improvements in all physical condition components (p < 0.05). The Wilcoxon test revealed significant differences between pretest and posttest for pull-ups (p = 1.91e-06) and Illinois agility (p = 1.91e-06). Most athletes showed improvement from the “low” and “moderate” categories to the “moderate” and “high” categories. Circuit training proved to be an effective method for improving physical condition in football players, particularly in muscular endurance, speed, agility, and cardiorespiratory endurance.